LITERATURE STUDY OF ISLAMIC ECONOMICS AND FINANCE ARTICLES IN SCOPUS-INDEXED JOURNALS IN THE LAST THREE YEARS - Furqonul Haq (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The study aimed to find the authors of Islamic economics and finance articles in Scopus-indexed journals for the last three years (2019-2021). The research method with a qualitative descriptive approach. Data collection techniques were obtained by studying documentation (Scopus website). The results showed that the authors of articles on Islamic economics and finance during the 2019-2021 period came from the United Kingdom, Malaysia, Indonesia, Turkey, New Zealand, Iran, the United States, Bahrain and India. During the 2019-2021 period, it can be explained that the authors of articles on the theme of Islamic banking and Islamic accounting come from England; authors of articles on Islamic business themes come from Malaysia and Indonesia; Islamic marketing-themed article writers from Turkey, Indonesia, Malaysia and New Zealand; the author of the article on the Islamic monetary theme comes from Indonesia; the authors of articles on the theme of Islamic insurance come from Malaysia and Iran; authors of articles on the theme of Islamic microfinance come from Malaysia and the United States; the author of the article on the Islamic fintech theme comes from Bahrain; authors of zakat-themed articles come from Indonesia, Malaysia and India; the author of the waqf theme article comes from Malaysia; the author of the article on the theme of the halal industry comes from Indonesia.